PENERAPAN KURIKULUM MERDEKA PADA MATA PELAJARAN FIQIH KELAS IV A DI MIN 9 BIREUEN (Pascasarjana Institut Agama Islam Almuslim Aceh, 2025)
Education in Indonesia has undergone several changes to the curriculum system with the aim of improvement. The efforts made by the government to improve it are changing and providing curriculum innovation. These include the KTSP/2006 curriculum becoming the 2013 Curriculum and becoming the Independent Learning Curriculum. This research uses a qualitative method based on field research, carried out at MIN 9 Bireuen. The findings of this research are: Freedom to learn is a policy of the Ministry of Education and Culture of the Republic of Indonesia. The Independent Curriculum is implemented with the aim of training students' independence in thinking. Independent learning prioritizes students' interests and talents which can foster creative and fun attitudes in students. The implementation of the independent curriculum in the learning process used in the Fiqh class IV A subject at MIN 9 Bireuen is carried out through planning and implementation